The Effects of Nine-Week Summer Vacation: Losses in Mathematics and Gains in Reading. Issue 6 (2015) - Paechter, Manuela; Luttenberger, Silke; Macher, Daniel; Berding, Florian; Papousek, Ilona; Weiss, Elisabeth M.; Fink, Andreas
No abstract available